2011
DOI: 10.1089/vbz.2010.0158
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study Assessing the Effectiveness of Long-Lasting Permethrin-Impregnated Clothing for the Prevention of Tick Bites

Abstract: Introduction: Tick-borne diseases such as Lyme disease, Rocky Mountain spotted fever, and ehrlichiosis are a significant concern for many thousands of workers who have frequent and unavoidable exposure to tick-infested habitats. Many North Carolina state employees with outdoor occupations report multiple tick bites each year, indicating that existing tick preventive strategies may be underutilized or ineffective. Treatment of clothing with permethrin, a nontoxic chemical with insecticidal, knockdown, and repel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 40 publications
1
32
0
1
Order By: Relevance
“…LLPI clothing is efficacious against other arthropod vectors, such as ticks and chiggers, as has been demonstrated in two U.S. studies 17,18 and in a recent German study. 6 Work by WilderSmith and others indicate that LLPI clothing would be a costeffective and acceptable means of preventing dengue.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…LLPI clothing is efficacious against other arthropod vectors, such as ticks and chiggers, as has been demonstrated in two U.S. studies 17,18 and in a recent German study. 6 Work by WilderSmith and others indicate that LLPI clothing would be a costeffective and acceptable means of preventing dengue.…”
Section: Discussionmentioning
confidence: 67%
“…We first conducted an open-labeled study of 16 North Carolina Division of Water Quality worker subjects, and found a 94% protective efficacy over a 1-year period. 17 We then conducted an RCT with 159 North Carolina parks and forestry rangers; the protective efficacy was 83% in the first year, but only 36% in the second year. 18 This study suggests that treated clothing had lost its efficacy over a period of 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…168,169 Regardless of the geographic location of the field work, permethrintreated clothing has been demonstrated to be highly effective at reducing tick bites and would be recommended for those veterinarians and assistants with occupational exposures. 170 Animals may act as mechanical carriers for ticks, and it is important to check patients as they enter a clinic to limit introduction of arthropod vectors into the indoor work environment. 171 Integrated pest management is the recommended approach to the control of rodents and vectors in veterinary medical buildings.…”
Section: Rodent and Vector Controlmentioning
confidence: 99%
“…The European Food Safety Authority reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. (Vaughn and Meshnick, 2011) Impregnated clothing Efficacy of 0.93 recorded 180 days after application.…”
Section: Disclaimermentioning
confidence: 99%